EXPERIMENTAL STUDY ON PROPERTIES OF CONCRETE USING BOTTOM ASH WITH ADDITION OF POLYPROPYLENE FIBER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The present research work has been carried out to evaluate the feasibility of utilization of coal bottom ash as fine aggregate in concrete and Polypropylene fibre is additionally used to enhance the strength characteristics of concrete. The concrete mix of M25 grade is prepared for different combinations of 0%, 10%, 20% and 30% of replacement of sand by bottom ash with 0.5%, 1.0%, 1.5% polypropylene fibre by total weight of taken Cube. The durability properties of concrete after 28days of curing age are tested.